2018
DOI: 10.1523/eneuro.0370-17.2018
|View full text |Cite
|
Sign up to set email alerts
|

AhR Deletion Promotes Aberrant Morphogenesis and Synaptic Activity of Adult-Generated Granule Neurons and Impairs Hippocampus-Dependent Memory

Abstract: Visual Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 65 publications
3
17
0
Order By: Relevance
“…Low AHR signaling triggered restorative ependymoglial proliferation after acute injury, while high AHR signaling promoted ependymoglial differentiation toward post-mitotic neurons after injury [45]. Also, another study reported that tamoxifen-inducible Nestin-Cre AHR deletion after postnatal day 30 increased adult hippocampal neurogenesis in nonstroke mice [46], which is in line with our findings that AHR plays a role in regulation of adult neurogenesis. However, the function of adult-born neurons after stroke remains unknown.…”
Section: Discussionsupporting
confidence: 91%
“…Low AHR signaling triggered restorative ependymoglial proliferation after acute injury, while high AHR signaling promoted ependymoglial differentiation toward post-mitotic neurons after injury [45]. Also, another study reported that tamoxifen-inducible Nestin-Cre AHR deletion after postnatal day 30 increased adult hippocampal neurogenesis in nonstroke mice [46], which is in line with our findings that AHR plays a role in regulation of adult neurogenesis. However, the function of adult-born neurons after stroke remains unknown.…”
Section: Discussionsupporting
confidence: 91%
“…Granule cells of the dentate gyrus in Ahr −= − mice show a similar morphological phenotype to the phenotype we observed in TCDD-exposed mice, namely higher arborization in proximal apical dendrites and a shorter apical length (de la Parra et al 2018). This similarity could suggest that TCDD exposure disrupts the physiological role of AHR, resulting in similar phenotypes in loss of AHR and TCDD exposure models.…”
Section: Brain Morphology Outcomes Of Gestational Low-dose Tcdd Exposuresupporting
confidence: 77%
“…AHR expression has also been detected in the spinal cord, as reported in the Human Protein Atlas [69]. The significance of Ahr in CNS glial and neuronal cells has been further illustrated by the phenotype of mice lacking functional AHR protein, impacting neurogenesis [70][71][72].…”
Section: Ahr Expression In the Central Nervous System (Cns)mentioning
confidence: 76%